2021
DOI: 10.1111/cas.14835
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐tumor efficacy of human anti‐c‐met CAR‐T cells against papillary renal cell carcinoma in an orthotopic model

Abstract: Papillary renal cell carcinoma (PRCC) is the second most common type of renal cancer after clear cell renal cell carcinoma (CCRCC), accounting for approximately 10%-20% of renal cancers. [1][2][3] It is classified into 2 main subtypes, type-1 and type-2. Type 1 is characterized by papillae and tubular structures covered with small cells containing basophilic cytoplasm and a small, uniform, oval nuclei. It is often multifocal but rarely recurs or metastasizes, and has a good prognosis, however in advanced cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 63 publications
0
22
0
Order By: Relevance
“…Jun-Ich Mori Et al. ( 25 ) also combined c-Met-CAR-T cells with axitinib, which once again demonstrated that molecular targeted drugs can synergically enhance the antitumor efficacy of CAR-T cells. Preclinical trials using CAR-T cells in combination with chemotherapy and radiation for PCa have shown significant mutually reinforcing effects ( 28 , 30 ).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Jun-Ich Mori Et al. ( 25 ) also combined c-Met-CAR-T cells with axitinib, which once again demonstrated that molecular targeted drugs can synergically enhance the antitumor efficacy of CAR-T cells. Preclinical trials using CAR-T cells in combination with chemotherapy and radiation for PCa have shown significant mutually reinforcing effects ( 28 , 30 ).…”
Section: Discussionmentioning
confidence: 96%
“…Furthermore, Jun-Ich Mori et al. ( 25 ) constructed c-Met-targeted CAR-T cells and validated the antitumor efficacy of c-Met-CAR-T cells in situ mouse models derived from clinical renal papillary cell carcinoma tissues. The c-Met-CAR-T cells have been demonstrated to infiltrate tumor tissues and inhibit tumor growth.…”
Section: Car-t Cells For Urologic Neoplasmsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a human c-Met–expressing mesothelioma xenograft in NOD SCID immunodeficient mice, c-Met CAR-T cells produced tumor regression 88 . c-Met CAR-T cells have also demonstrated antitumor activity in NSCLC, renal cell, and gastric epithelial cancer models 89–91 . In a phase 0 study (NCT01837602) in 6 patients with metastatic breast cancer, intratumoral injection of mRNA-transfected c-Met CAR-T cells was tolerated and evoked an inflammatory response within tumors 92 .…”
Section: Targeting the Hgf/c-met Pathwaymentioning
confidence: 99%
“…Akihiro Ishikawa and Masazumi Waseda contributed equally to this work. Podoplanin (PDPN) is a mucin-type transmembrane protein with a glycosylated extracellular domain that is overexpressed in various cancers, such as brain, oral, and lung cancers (Breiteneder-Geleff et al, 1997;Chu et al, 2005;Kahn et al, 2002;Kato et al, 2003Kato et al, , 2004Mishima et al, 2006;Schacht et al, 2005), and is considered a promising therapeutic target for cancer treatment (Kreppel et al, 2010;Mori et al, 2021;Waseda & Kaneko, 2020). To target PDPN, we previously focused on the rat anti-human PDPN antibody (NZ-1), which recognizes PDPN specifically (Kato et al, 2006).…”
Section: Introductionmentioning
confidence: 99%